Is It Legitimate for Society to Intervene in the Way Citizens Live Their Lives When the Cost of Health Care Has to Be Borne by the General Public?—General Considerations and Special Implications During the Covid-19 Pandemic - Edlinger, Christoph; Klein, Dominic; Lichtenauer, Michael (Frontiers in Public Health, 2021)
Over the last few decades, the perception of disease has changed significantly. In the concept of the sick person's role it should be the aim of every person to keep health at a good level for as long as possible. Several examples can be found where, however, a disease can be caused or worsened by a person. Examples include unhealthy diet, alcohol consumption leading to atherosclerosis and diabetes, or smoking, leading to lung cancer and COPD. There are also other appropriate examples where there is a potential for conflict between the autonomy of the individual and health. Improving public health should be the main objective of any health system. However, the more the impact is on personal freedom (and there is no extraneous danger), the more an attempt should be made to achieve this through the motivation of each individual to support the desire for a healthy lifestyle, rather than through legal prohibitions or penalties. The situation is even more complex in the case of the Covid-19 pandemic. In this context too, personal freedom is restricted in many areas and some people feel, for example, that compulsory masks or the prohibition of large crowds are serious encroachment on their autonomy. However, even in this case, the risk of possible external threats from the spread of the virus outweighs the right to personal choice and freedom. To sum up, it is necessary to balance the two principles - autonomy and interference in them in the interests of public health.